Event management system for career fair - Lee, Wen Xuan (2024)
In the current event management system market, there are many versatile tools that cater to a wide range of events such as corporate meetings and entertainment activities. These systems offer comprehensive features including attendee registration, event scheduling, ticketing, and basic engagement options, making them suitable for a variety of event types. However, there's a noticeable gap in their functionality when it comes to specialized events, particularly those in the career sector. Therefore, this project aims to address this gap by introducing features that are specifically designed for the unique requirements of career event. This includes a sophisticated module dedicated to managing the complex schedules of career fairs, which typically involve various sessions, workshops, and exhibit booths. This module is tailored to meet the dynamic nature of these events. In addition, the system will provide a space for alumni from various professional backgrounds to connect with attendees, fostering networking opportunities and facilitating mentorship relationships. This feature aims to bridge the gap between aspiring professionals and seasoned industry experts, enhancing the career development experience at the fair. Another notable feature is the use of QR code technology for various purposes, such as providing quick access to information at booths and streamlining the event check-in process, thereby enhancing the overall experience for both organizers and attendees. The development of this system begins with an exhaustive background analysis to identify the deficiencies in current event management applications, particularly their inadequacy in meeting the needs of career fairs. Subsequently, a comprehensive literature review is conducted to examine existing systems and grasp the specific requirements of career-related events. The project’s scope and objectives are then clearly outlined, with a focus on crafting a system that seamlessly integrates detailed program management, alumni networking features, and advanced QR code functionalities tailored for career fairs. This strategic approach aims to address the unique challenges associated with managing career fairs while enhancing efficiency, engagement, and the overall event management process in this domain.